(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Increasing food demands along with shrinkage of agricultural lands make urban dwellers vulnerable to food insecurity. This leads to practice rooftop gardening (RTG) by the dwellers living in an urban area. The present research assessed the potentiality of rooftop gardening as a supplement to urban household food and nutrition resilience in Dhaka city of Bangladesh. The study follows a mix-method approach (i.e. qualitative and quantitative) to fulfill the objectives. Currently, the city has 257.95 ha area of RTG (i.e. 0.32% of 80,220 hectares of continuous roofs), which can fulfill the demand of about 0.3% fresh vegetables and fruits of the dwellers of Dhaka city. Moreover, yearly practices of RTG by the inhabitants of the city can contribute about 362 million BDT. The present study shows that contribution to household level resilience for vegetables and fruits produced from RTGs are about 6% and 18% respectively. The RTG practitioners consume about 75% cultivated fruits and vegetables. Utilization of rooftop spaces for gardening could be a potential solution to household food and nutrition insecurity in DMA. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 59-67